Dinamika Ketahanan Sosial Wilayah Pada Pemilu Serentak 2024 (Studi Di Provinsi DKI Jakarta) - Karyono, Karyono; Riyanta, Stanislaus; Daryanto, Eko (Jurnal Ketahanan Nasional, 2024)
The vulnerability of the Governor Election originating from the political dimension had a potential impact on regional social resilience in DKI Jakarta Province because it threatened the unity and integrity of the nation in general and the social harmony of the DKI Jakarta community as happened in the 2017 DKI Jakarta elections. The effect also occurred in the 2019 presidential election because of the division of society in the implementation of the 2019 DKI Jakarta elections. This background had become the researcher's curiosity to captured the implementation of the Governor Election 2024 in DKI Jakarta Province through data collection from November to December 2023. This research used mixed methods through quantitative data collection from IKP 2024 as secondary data to be tested with alternative vulnerability measurements from qualitative data through semi-structured interview techniques from 27 informants. The vulnerability analysis method used was from the perspective of Hank Prunckun. As fact finding as the root cause of the problem and the fundamental source of the vulnerability was the existence of a black campaign using SARA issues so that some strategies needed to be formulated to mitigated the risk. The formulation of the strategies that could be delivered include: [1] Using of the Law No. 7/2017 and the authority and function of Bawaslu institutionally to optimized the existence of Gakkumdu to took firm action against black campaigns with SARA issues so that the community harmony on DKI Jakarta Province was maintained; and [2] Using of the Law No. 7/2017 and the authority and function of Bawaslu institutionally to optimized the existence and social functions of the Religious Leaders (Toga), the Traditional Leaders (Todat), the Community Leaders (Tomas), and the Community Communication Forums in DKI Jakarta Province to educated the public that the blackcampaigns with SARA issues were not in accordance with the noble values of the Indonesian Nation so that the community harmony on the DKI Jakarta Province was maintained..